Development of sustainable waste bank business models: A PRISMA-based systematic literature review - Shanti Ike Wardani; Nunuk Latifah (International Journal of Applied Finance and Business Studies, 2026)
The social and community dimensions of development are often complicated. The community and environmental problems can, however, be addressed with sociopreneurship, the social entrepreneurship and waste management system with the creation of waste banks. Nonetheless, banks are troubled by operational and sustainability issues. This study aims to develop a sociopreneurial waste bank business model. The author conducted a systematic literature review (SLR) based on PRISMA guidelines and examined 15 articles in the Google Scholar database. The results identified three operational models of waste banks (independent, partnership, corporatization) along with their internal and external challenges. This study proposes a sustainable sociopreneurship framework with five integrative characteristics: social value creation, social innovation, market orientation, social organization, and financial sustainability. It is concluded that a hybrid model, which combines the strengths of various models and is supported by digitalization, is the best path for waste bank sustainability. The implication of this research is a contribution to the development of sustainable social business models and provides a basis for further research regarding implementation and impact measurement.